Facts about Vitamin A - Nan C. Jensen; Linda B. Bobroff (EDIS)
Revised! FCS8639, a 2-page fact sheet by Nan C. Jensen and Linda B. Bobroff, answers questions about this fat-soluble vitamin that is essential to our health. Published by the UF Department of Family Youth and Community Sciences, December 2009.